Sistema de control automático de temperatura para una plataforma de caracterización de SiPM en el laboratorio de Villavicencio (2021)
The present research aimed to improve the characterization platform of silicon photomultipliers with analogue temperature control, for its execution a quantitative, descriptive methodology was used under an experimental approach, for its development five phases were carried out, the first one consisted in establishing the parameters for the redesign of the plant structure, the second phase was the identification and modeling of the plant, the third the design and implementation of the interface, the fourth phase the adaptation of temperature control and analog implementation and the fifth phase which consisted of integrating and testing the graphical interface, the plant and the analog controller. In the same way, the LM35 sensors, the HTC 1500 controller and the MatLab program were used as instruments, obtaining as results a significant improvement in profit of the plant.